A Package for Measuring Emergence, Self-organization, and Complexity Based on Shannon Entropy - Santamaría-Bonfil, Guillermo; Gershenson, Carlos; Fernández, Nelson (Frontiers in Robotics and AI, 2017)
We present Matlab/Octave functions to calculate measures of emergence, self-organization, and complexity of discrete and continuous data. The measures are based on Shannon's information and differential entropy, respectively. Examples from different datasets and probability distributions are used to illustrate the usage of the code.